Peningkatan Efektivitas Pengelolaan Keuangan dan Strategi Pemasaran untuk Mengoptimalkan Penjualan - Gandawijaya, Carissa; Leffiana, Rachelle Viensisca; Pandita, Dominicus Hanschen; Arleta, Chelsea; Dior, Daido Van; Keane, Roy; Deven, Deven; Tauryawati, Mey Lista (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, particularly in terms of employment generation and national economic resilience. However, many MSMEs face challenges in financial management and marketing, especially in the era of digitalization. This research examines the implementation of the Community Development Program KUM-017 in Sangkanerang Village, Kuningan, West Java, focusing on empowering the Wedang Jahe Binangkit MSMEs. The program aims to enhance financial performance, operational efficiency, and marketing strategies through educational approaches and the implementation of Standard Operating Procedures (SOPs). Methods include field studies, data analysis, and direct mentoring. Results show significant improvements in financial record-keeping, SOP development, and digital marketing strategies, despite challenges in adapting to change and human resources. The study concludes by emphasizing the importance of effective financial management and marketing as key drivers for enhancing competitiveness and growth of MSMEs. Programs like this contribute positively and can be widely applied to support MSME growth in Indonesia, alongside efforts to strengthen the local economy and improve community welfare.